2007
DOI: 10.1149/1.2721760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Annealing on Ga-Doped ZnO Films Prepared by Magnetron Sputtering

Abstract: In this study, Ga-doped ZnO ͑GZO͒ films deposited on a sapphire utilizing magnetron cosputtering method using ZnO and Ga 2 O 3 targets were demonstrated. The results revealed that the resistivities of the GZO films reduced by at least two orders of magnitude after the thermal annealing. The reduction in resistivity could be attributed not only to the activation of Ga dopants and to the increase of electron mobility, but also to the enlargement of the grain size that occurred as a result of thermal annealing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 30 publications
0
43
1
Order By: Relevance
“…When the annealing temperature is increased, the absorption edge moves to shorter wavelength and the average optical transmittance increases. The shift of absorption edge with annealing temperature is due to the increase of carrier concentration of thin films and is explained by the Burstein-Moss effect, where the conduction band becomes filled at high carrier concentration and the lowest energy states in the conduction band are blocked (Oh, Jeong, Kim, Lee, & Myoung, 2005;Sheu, Shu, Lee, Tun, & Chi, 2007). Fig.…”
Section: Electrical Propertymentioning
confidence: 97%
“…When the annealing temperature is increased, the absorption edge moves to shorter wavelength and the average optical transmittance increases. The shift of absorption edge with annealing temperature is due to the increase of carrier concentration of thin films and is explained by the Burstein-Moss effect, where the conduction band becomes filled at high carrier concentration and the lowest energy states in the conduction band are blocked (Oh, Jeong, Kim, Lee, & Myoung, 2005;Sheu, Shu, Lee, Tun, & Chi, 2007). Fig.…”
Section: Electrical Propertymentioning
confidence: 97%
“…At lower annealing temperature (≤200 • C), the film resistivity decreased with the increment of annealing temperature. The main reason is that the crystalline grain size became larger resulted in the amount of trapping states reduced [24]. As annealing temperature was more than 200 • C, the film resistivity rapidly raised which associated with the more zinc acceptor impurities were activated to recombine with the oxygen resulted in reduction of oxygen vacancies [19,25].…”
Section: Zito Electrode (Zn Atomic Concentration Ratio Of 58%)mentioning
confidence: 99%
“…Numerous studies have reported the deposition of ZnO:Ga films with variation deposition techniques such as atomic layer deposition (Maeng and Park, 2013), sol-gel method (Lin et al, 2010), chemical vapour deposition (Yang et al, 2009), physical vapour deposition (Lee, 2013), pulsed laser deposition (Shin et al, 2009), magnetron sputtering (Sheu et al, 2007), DC reactive magnetron sputtering (Ma et al, 2007) and RF sputtering (Yu et al, 2005). It has been reported that the properties of ZnO:Ga thin films are dependent on the deposition methods.…”
Section: Introductionmentioning
confidence: 99%